2002
DOI: 10.1016/s1534-5807(02)00149-1
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Leptin Action and Regulation of Obesity by Protein Tyrosine Phosphatase 1B

Abstract: Common obesity is primarily characterized by resistance to the actions of the hormone leptin. Mice deficient in protein tyrosine phosphatase 1B (PTP1B) are resistant to diabetes and diet-induced obesity, prompting us to further define the relationship between PTP1B and leptin in modulating obesity. Leptin-deficient (Lep(ob/ob)) mice lacking PTP1B exhibit an attenuated weight gain, a decrease in adipose tissue, and an increase in resting metabolic rate. Furthermore, PTP1B-deficient mice show an enhanced respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
393
2
8

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 497 publications
(415 citation statements)
references
References 36 publications
12
393
2
8
Order By: Relevance
“…When these animals are subjected to the stress of a high fat diet, they show protection against diabetes and obesity through increased phosphorylation of signaling components associated with the insulin, leptin, and growth hormone receptors (12)(13)(14)(15)46). In response to Fas activation, a known stress inducer, we have shown, in PTP1B-null mice but not WT mice, elevated tyrosine phosphorylation and downstream signaling of receptor tyrosine kinases involved in liver injury, namely the Met receptor tyrosine kinase.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…When these animals are subjected to the stress of a high fat diet, they show protection against diabetes and obesity through increased phosphorylation of signaling components associated with the insulin, leptin, and growth hormone receptors (12)(13)(14)(15)46). In response to Fas activation, a known stress inducer, we have shown, in PTP1B-null mice but not WT mice, elevated tyrosine phosphorylation and downstream signaling of receptor tyrosine kinases involved in liver injury, namely the Met receptor tyrosine kinase.…”
Section: Discussionmentioning
confidence: 76%
“…PTP1B-null mice show hyperphosphorylation of the insulin receptor in liver and muscle tissue upon stimulation with insulin (12,13). Moreover, these mice are resistant to weight gain caused by a high fat diet through the ability of PTP1B to regulate the leptin receptor, via dephosphorylation and subsequent termination of signaling from the downstream kinase Jak2 (14,15). PTP1B has also been shown to interact with a number of SH3 domain-containing proteins through its proline-rich motifs, including p130Cas (3), p62Dok (16), ␤-catenin (17), Grb2, and Crk (3), which are thought to target this phosphatase to distinct cellular protein complexes.…”
mentioning
confidence: 99%
“…Of particular interest, gene-targeting studies in mice have established PTP1B as a critical physiological regulator of metabolism by attenuating insulin, leptin, and growth hormone signaling (2)(3)(4)(5)(6). PTP1B function seems to be dispensable for embryonic development.…”
mentioning
confidence: 99%
“…Aberrant tyrosine phosphorylation levels have been associated with the development of cancer, autoimmunity, and diabetes, thus indicating that PTPs might play important etiological and pathogenic roles in these diseases (1)(2)(3)(4)(5). In particular, two elegant studies with PTP1B knockout mice, in which increased insulin sensitivity and resistance to diet-induced obesity were observed (6,7), indicated that PTP1B is an important negative regulator of insulin and leptin action, suggesting that inhibition of this enzyme could augment and prolong insulin and leptin signaling (8,9). As a result, a number of academic and industrial laboratories have devoted considerable efforts toward the development of selective inhibitors of PTP1B for treatment of type 2 diabetes and obesity resulting in very significant progress (reviewed in Refs.…”
mentioning
confidence: 99%